Arterial hypertension in immediate postoperative period after valve replacement. Issue 7 (July 1978) - Estafanous, F G; Tarazi, R C; Buckley, S; Taylor, P C
Abstract : Paroxysmal hypertension occurred during the first 8 hours after cardiac valve replacement in 15 of 186 consecutive patients. The clinical characteristics of this hypertension were similar to those of hypertension after myocardial revascularization, except that this complication occurred much less frequently after valve replacement (8.1%) than after myocardial revascularisation (33%) (P less than 0.001). Hypertension resulting from hypoxia, hypercapnia, shivering, or arousal from anaesthesia was excluded from consideration. The rise in systemic arterial pressure (average 34/35 mmHg +/- 4.9/4.3 SE) was usually associated with a reduction in central venous pressure (12/15 patients) and a mild increase (2 to 4 cm saline) in left atrial pressure. The incidence of hypertension was not related to the valve replaced (aortic or mitral), type of lesion (stenosis or regurgitation), preoperative level of blood pressure, or use of hypothermia during operation. However, none of the 18 patients who had double valve replacement showed significant rise in blood pressure after operation. It is suggested that these hypertensive episodes may be related to pressor reflexes from the heart and/or great vessels.